The effects of warming and ocean acidification on growth, photosynthesis, and bacterial communities for the marine invasive macroalga Caulerpa taxifolia. (1st November 2017) - Roth‐Schulze, Alexandra J.; Thomas, Torsten; Steinberg, Peter; Deveney, Marty R.; Tanner, Jason E.; Wiltshire, Kathryn H.; Papantoniou, Stephanie; Runcie, John W.; Gurgel, C. Frederico D.
Abstract: Caulerpa taxifolia is a pantropical green benthic marine macroalga, and one of the best known marine invasive species in temperate coastal habitats. In Australia, this species has been introduced to seven estuaries along New South Wales and one in South Australia. How this alga will perform under future climate change scenarios is however not well defined. This study experimentally assessed the effects of ocean acidification and global warming on the growth, photosynthetic performance and the bacterial community on two populations of C. taxifolia, one native and one invasive. A range of complex significant interactive effects between pH, temperature, and initial plant size on the growth of C. taxifolia were observed, but no effect of population origin and photosystem II (PSII) fluorescence quantum yield parameters were detected. No significant effects of the treatment combinations were observed on bacterial community richness or diversity. Only one bacterial species out of 1087 present on the algae showed significant changes between pH treatments at high temperature (24°C). This bacterium belonged to the genus Planctomyces and its relative abundance was more than 10 times higher in samples with low pH compared to the control. Higher plant growth was observed under all higher pCO2 and lower pH conditions suggesting that C. taxifolia will benefit from climate change, posing a potential higher risk in invaded locations.